Applying SiO2 nano-particles for improving optical properties of WLED conformal and in-cup structures - Phan Xuan Le; Pham Quang Minh (Institute of Advanced Engineering and Science, 2021)
This article is the analysis of SiO2 nano-particles’ influences on the luminous efficiency and the color temperature uniformity of a remote phosphor structure in a WLED. The purpose of integrating SiO2 into the silicone layer in the remote phosphor structure is to significantly promote the scattering occurrences. Particularly, with an appropriate proportion of SiO2, there could be more blue lights generated at large angles, leading to reducing the angular-dependent color temperature deviation. The luminous flux also can get benefits from SiO2 addition owing to a proper air-phosphor layer refractive index ratio provided by this SiO2/silicone compound. The attained experimental results were compared with optical values of a non-SiO2 remote phosphor configuration and showed a notable enhancement. The color deviation was reduced by approximately 600 K in the angles from -700 to 700. Additionally, the lumen efficiency was improved by 2.25% at 120 mA driving current. Hence, SiO2 can be used to boost both color uniformity and luminous efficacy for remote-phosphor WLED.